BHUx: A Patent Polyherbal Formulation to Prevent Atherosclerosis. Issue 2 (2005) - Tripathi, Yamini B.; Singh, Birendra K.; Pandey, Ravi S.; Kumar, Mohan
Abstract : Ayurvedic medicine is a time-tested system of medicine which has been in clinical use for centuries in India. Being a time-tested system, it has an edge over other existing systems of health management, especially for dealing with chronic disorders such as coronary artery disease, which is of a complex multi-etiological nature. Recently, we have shown that BHUx, a patented polyherbal formulation consisting of the aqueous fraction of five medicinal plants of the ayurvedic system, has significant anti-inflammatory properties through inhibition of cyclooxygenase-2 and lipoxygenase-15. Here we have investigated its effect on diet-induced atherosclerosis in albino rabbits. BHUx was given orally for 3 months to rabbits pre-treated with an atherogenic diet for 3 months. After 6 months, the dorsal aorta was processed for histological studies for calcium and collagen content. The results demonstrated a remarkable reduction in intimal thickening in the treated animals. In addition, there was less calcification at the intima–medial interface and increased intensity of collagen cap on the surface along with an increase in survival, compared with the sham control. We suggest that BHUx is a potent, multi-factorial formulation against atherosclerosis.